Predictors and intervening variables of talent retention - Mohd Rasdi, Roziah; Kusnin, Nurhazimah; Yong, See Chen (Human Resource Management Academic Research Society, 2018)
Retaining the best talent is one of the major factors towards achieving a high-income nation, and it is critical to organizational success. Organizations have introduced various strategies to enhance employee retention, and efforts should be targeted at valuable, contributing employees such as the high skilled workers. Failure to retain the best talent in organization implicated substantial losses to organization in terms of investment, assets, and destruct social and communication structures as well as affect other employees’ morale and work behaviour. Thus, it is imperative to investigate the predictors of talent retention that serve as the engagement and motivational drivers for employee to retain in an organization. Our review of related literature found that potential predictors such as high performance work system, job embeddedness and work life balance have been associated with employee’s inclination to remain in organization. Intervening factors such as intrinsic rewards and generational cohort are found to influence the relationships between the predictors and talent retention.